Human development and hedonism culture challenges: a review from islamic perspective / Halipah Hamzah - Hamzah, Halipah (2016)
Islamic development consists of human development, material development, technology development, and development of knowledge. Major aspect of Islamic development is human development. Human development is the process of human change to a better condition includes elements of physical, intellectual, spiritual and emotional. Spiritual and physical developments should be given priority in human development because of the negligence of one of these aspects lead to the imperfections in life for individuals, communities and countries. In the process of human development, there are many challenges to be faced. Among them are the challenges arising from cultural phenomenon hedonism. This culture brings challenges to the characteristics of human development, among which are a challenge to faith, knowledge, morality, justice and so on.